PENGEMBANGAN SOSIAL ANAK USIA DINI DENGAN TEMAN SEBAYA DI TK ISLAM KHAIRA UMMAH KOTA PADANG - Nofrika, Diana Sahara; Izzati, Izzati (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract: This research is motivated by the social development of early childhood with peers in the Islamic Kindergarten Khaira Ummah Ikur Koto Koto Padang City. The research used descriptive qualitative research approach. To see how the Early Childhood Social Development with Sebya Friends in the Khaira Islamic Kindergarten Ummah Ikur Koto Koto Tangah, Padang City. Children studied class B4 in the Islamic Kindergarten Khaira Ummah Ikur Koto Koto Tangah, Padang City. The informants of this study were teachers in the Islamic Khaira Kindergarten Ummah Ikur Koto Koto Tangah, Padang City. Data collection uses observation, interviews and documentation. Based on data shows that in the IslamicKindergarten Khaira Ummah Ikur Koto Koto Tangalh Padang City there are several children who demonstrate social development with peers and children who have not developed socially with peers.